Navigating entrepreneurial challenges: the role of mindset in shaping female entrepreneurship in Senegal - Coulibaly, Diarra (2024)
This research explores the complex interplay between the entrepreneurial mindset and the socio-economic barriers impacting female entrepreneurs in Senegal. Anchored by the research question «How does the entrepreneurial mindset contribute to overcoming challenges hindering female entrepreneurship in Senegal?” an explorative qualitative research approach is employed. Data was gathered through in-depth interviews with female entrepreneurs in the Dakar region. Utilizing both thematic and phenomenological analyses, the study probes the individual experiences and perceptions of these entrepreneurs. The findings illustrate that while the entrepreneurial mindset endows women with essential skills such as resilience, emotional endurance, strategic innovation, proactiveness and adaptability, these alone are insufficient to surmount all obstacles. The study identifies a range of socio-economic challenges, including limited access to capital and market constraints, which significantly hinder operational and strategic opportunities for women. Notably, gender emerges as a nuanced factor; it presents both challenges, through societal norms and roles, and opportunities, through targeted support mechanisms and networks that uniquely benefit female entrepreneurs. The thesis contributes to the discourse on female entrepreneurship by delineating how socio-economic and gender-specific dynamics interact with entrepreneurial mindsets. It advocates for targeted policy interventions and a supportive entrepreneurial framework that acknowledges the unique hurdles and advantages faced by women. Recommendations for future research include broadening the geographic scope and incorporating objective psychological assessments to enhance the phenomenological analysis of entrepreneurial traits and to better understand the evolving dynamics of female entrepreneurship.